Rola zakażenia Helicobacter pylori w patogenezie centralnej surowiczej choroidopatii - Misiuk-Hojło, Marta; Michałowska, Magdalena; Żołyńska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Central serous chorioretinopathy (CRS) is a serous macular detachment that usually affects young people and leads fortunately to a spontaneous resolution and a good visual prognosis in most patients. The etiopathogenesis of the disease is still not completely understood and no effective treatment is available at this time. However, an association has been recently highlighted between Helicobacter pylori infection and CRS connected with pathology of retinal vessels.